A replication-deficient H9N2 influenza virus carrying H5 hemagglutinin conferred protection against H9N2 and H5N1 influenza viruses in mice - Ren, Weigang; Pei, Shuli; Jiang, Wenming; Zhao, Meixia; Jiang, Le; Liu, Honggang; Yi, Yongxiang; Hui, Mizhou; Li, Junwei (Frontiers in Microbiology, 2022)
H5N1 and H9N2 influenza viruses have been reported to cause human infections and are believed to have a pandemic potential. Vaccine is an effective tool to prevent influenza virus infection. However, inactivated influenza vaccines sometimes result in low antigenicity as a result leads to generating of incomplete immune protection in the form of low cellular and humoral immunity. While the low temperature adapted, traditional live attenuated influenza vaccine (LAIV) is associated with the potential risk to revert to a virulent phenotype, there appears an essential need for an alternative potent methodology to design and develop influenza vaccines with substantial safety and efficacy which may confer solid protection against H9N2 or H5N1 influenza virus infections. In the present study, a replication-deficient recombinant influenza virus, WM01ma-HA(H5), expressing hemagglutinin (HA) of both H9N2 and H5N1 subtypes was developed. The chimeric gene segment expressing HA(H5), was designed using the sequence of an open reading frame (ORF) of HA adopted from A/wild duck/Hunan/021/2005(H5N1)(HN021ma) which was flanked by the NA packaging signals of mouse-adapted strain A/Mink/Shandong/WM01/2014(H9N2) (WM01ma). Due to the absence of ORF of structural protein NA, the replication of this engineered H9N2 influenza viruses WM01ma-HA(H5) was hampered in vitro and in vivo but was well competent in MDCK cells stably expressing the NA protein of WM01ma. Intranasal vaccination of mice with WM01ma-HA(H5) stimulated robust immune response without any clinical signs, and conferred complete protection from infection by H5N1 or H9N2 subtype influenza viruses.